Perspectives on the Great Amazon Reef: Extension, Biodiversity, and Threats - Francini-Filho, Ronaldo B.; Asp, Nils E.; Siegle, Eduardo; Hocevar, John; Lowyck, Kenneth; D'Avila, Nilo; Vasconcelos, Agnaldo A.; Baitelo, Ricardo; Rezende, Carlos E.; Omachi, Claudia Y.; Thompson, Cristiane C.; Thompson, Fabiano L. (Frontiers in Marine Science, 2018)
Here we provide a broad overview of the Great Amazon Reef System (GARS) based on the first-ever video surveys of the region. This footage supports four major hypotheses: 1) the GARS area may be six times larger than previously suggested (up to 56,000 km2); 2) the GARS may extend deeper than previously suggested (up to 220 m); 3) the GARS is composed of a greater complexity and diversity of habitats than previously recognized (e.g. reef platforms, reef walls, rhodolith beds, and sponge bottoms); and 4) the GARS represents useful system to test whether a deep corridor connects the Caribbean Sea to the Southwest Atlantic Ocean. We also call attention to the urgent need to adopt precautionary conservation measures to protect the region in the face of increasing threats from extractive oil and gas practices. With less than 5% of the potential area of the GARS surveyed so far, more research will be required to inform a systematic conservation planning approach and determine how best to establish a network of marine protected areas. Such planning will be required to reconcile extractive activities with effective biodiversity conservation in the GARS.